An Examination of the Impact of Control Risk, Negotiation, and Pricing Specialists in the Audit of Fair Value Measurements - Randle, Sr., Edward Charles (Journal of Accounting and Finance, 2022)
Academics, businesspeople, regulators, and investors continue to vigorously argue for and against the practice of using fair value accounting. Management is responsible for developing fair value measures and disclosures that are included in the financial statements. The auditor is tasked with obtaining sufficient evidence to provide reasonable assurance the organization’s fair value measures are following generally accepted accounting principles. Affecting the auditor’s responsibility is the increased use of valuation specialists, the impact of negotiation during the audit, and the control risk assessment. Examining the existing research, this review provides the audit practitioner with critical insights from the existing literature and serves as a practical guide for regulators (Martin et al., 2006).